Copper-Containing Alloy as Immunoregulatory Material in Bone Regeneration via Mitochondrial Oxidative Stress - Xu, Daorong; Qian, Jikun; Guan, Xin; Ren, Ling; Yang, Kaifan; Huang, Xuan; Zhang, Shuyuan; Chai, Yu; Wu, Xiaohu; Wu, Hangtian; Zhang, Xianrong; Yang, Ke; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
In the mammalian skeletal system, osteogenesis and angiogenesis are closely linked by type H vessels during bone regeneration and repair. Our previous studies confirmed the promotion of these processes by copper-containing metal (CCM) in vitro and in vivo. However, whether and how the coupling of angiogenesis and osteogenesis participates in the promotion of bone regeneration by CCM in vivo is unknown. In this study, M2a macrophages but not M2c macrophages were shown to be immunoregulated by CCM,. A CCM, 316L-5Cu, was applied to drilling hole injuries of the tibia of C57/6 mice for comparison. We observed advanced formation of cortical bone and type H vessels beneath the new bone in the 316L-5Cu group 14 and 21 days post-injury. Moreover, the recruitment of CD206-positive M2a macrophages, which are regarded as the primary source of platelet-derived growth factor type BB (PDGF-BB), was significantly promoted at the injury site at days 14 and 21. Under the stimulation of CCM, mitochondria-derived reactive oxygen species were also found to be upregulated in CD206hi M2a macrophages in vitro, and this upregulation was correlated with the expression of PDGF-BB. In conclusion, our results indicate that CCM promotes the evolution of callus through the generation of type H vessels during the process of bone repair by upregulating the expression of PDGF-BB derived from M2a macrophages.